Perspectives on COVID-19 and Sexual Health; a Letter to Editor - Shahrzad Nematollahi; Mitra Abdoli (Men's Health Journal, 2020)
The pandemic of coronavirus, known as COVID-19, has swept the world during the past several months. The exponential growth of this outbreak led World Health Organization to announce it as the sixth public health emergency of international concern on 30 January 2020 (1). Coronavirus is transmitted through direct contact with the patient (coughing, sneezing, respiratory droplets). Respiratory droplets spread through close contact from person to person (hugging, kissing, and patient care) can transmit coronavirus (2). There is also evidence of oral-fecal transmission (3-5). Despite the presence of angiotensin-converting enzyme (ACE2) as receptor of coronavirus in testicles, there is very little evidence of transmission through sexual contact with male patients (6). A study detected Coronavirus in seminal fluid of 34 recovered male patients with mild symptoms (7), but it has not been observed in semen of active COVID-19 patients. The lack of observation; undoubtedly, does not rule out the possibility of sexual transmission of coronavirus. On the other hand, there is no evidence of COVID-19 transmission by vaginal secretions through sexual contact or from mother to child (vertical transmission) (8-10).